Randomized Controlled Trial of Modified Nasobiliary Fixation and Drainage Technique - Mi, Na; Zhang, Shuting; Zhu, Zhili; Yu, Yan; Li, Wenjing; Zheng, Lu; Chu, Lingling; Li, Jing (Frontiers in Surgery, 2022)
Objectives:We investigatedthe clinical efficacy of a modified nasobiliary fixation and drainage technique which was designed in an attempt to reduce unplanned extubation and tube blockage and improve bile drainage and the comfort of catheterized patients. Methods:From January 2019 to December 2020, 230 patients receiving Endoscopic nasobiliary drainage (ENBD)during hospitalization were recruited to this study. Participants were randomly allocated to 2 groups by using the block randomization method: in the control group: the conventional method of nasobiliary fixation was adopted after surgery; in the test group: intraoperative annular cutting of nasobiliary tubes was performed and the exposed catheter length was standardized. The modified “tube-nose-ear” three-step technique was performed after surgery. The clinical efficacy of a modified nasobiliary fixation and drainage techniquewas evaluated and compared between the test group and the control group. Results: The rate of unplanned extubation and incidence of complications were significantly lower in the test group thanthe control group. In addition, the rate of bilirubin decrease after drainage was higher in the test group. Patient discomfortduring catheterization was alsosignificantly reducedusing the modified technique(P＜0.05). Conclusions: The modified technique of nasobiliary fixation and drainage technique can significantly reduce unplanned extubation and nasobiliary tube blockage after ENBD, facilitate biliary drainage, and improve patient comfort. This technique warrants wider application in clinical practice.